ANALYSIS OF INCOME AND BUSINESS DEVELOPMENT STRATEGY IN PALM OIL NURSERY SMEs IN SILANGKITANG DISTRICT - Arya Arabil; Tuty Ningsih (LPPM Universitas Malikussaleh - Indonesia, 2026)
Small and medium-sized enterprises (SMEs) engaged in oil palm nursery operations in Silangkitang Subdistrict face challenges such as the lack of proper financial record-keeping, limited production land, and the absence of a structured business development strategy. This study aims to analyze income and formulate a business development strategy for oil palm nursery SMEs in Silangkitang Subdistrict, South Labuhanbatu Regency, North Sumatra Province. The research was conducted from February to April 2026 using a mixed-methods approach combining quantitative and qualitative methods. Respondents were selected through purposive sampling, consisting of three business operators. Revenue analysis was performed by calculating total costs (TC), total revenue (TR), net income (π), the R/C ratio, and the break-even point (BEP), while business development strategies were formulated using SWOT analysis. The results of the study indicate that all oil palm nursery businesses in Silangkitang Subdistrict are viable and profitable, with an R/C ratio > 1: Respondent 1 at 3.18 with revenue of 154,350,000, Respondent 2 at 3.47 with revenue of Rp. 159,755,000, and Respondent 3 at 2.98 with revenue of Rp. 478,000,000. Based on the SWOT analysis, the business is positioned in Aggressive Strategy. The priority strategies formulated include increasing production capacity, expanding digital marketing through social media, improving financial record-keeping systems, and strengthening integrated pest management. Thus, palm oil nursery MSMEs in Silangkitang Subdistrict warrant aggressive development by leveraging available internal strengths and external opportunities. Keywords: SMEs, Oil Palm Nurseries, Revenue, Development Strategies, SWOT Analysis